Disrupting neuronal transmission: mechanism of DBS? - Chiken, Satomi; Nambu, Atsushi (Frontiers in Systems Neuroscience, 2014)
Applying high-frequency stimulation to deep brain rain structure, known as deep brain stimulation (DBS), has now been recognized an effective therapeutic option for a wide range of neurological and psychiatric disorders. DBS targeting the basal ganglia thalamo-cortical loop, especially the internal segment of the globus pallidus, subthalamic nucleus and thalamus, has been widely employed as a successful surgical therapy for movement disorders, such as Parkinson’s disease, dystonia and tremor. However, the neurophysiological mechanism underling the action of DBS remains unclear and is still under debate: does DBS inhibit or excite local neuronal elements? In this review, we will examine this question and propose the alternative interpretation: DBS dissociates inputs and outputs, resulting in disruption of abnormal signal transmission.